Mimicry of metal-free ceramic crown of an upper central incisor. Case report - Ochoa-Vázquez, Boris Lenin (2021)
Nowadays, dental aesthetics has a relevant role within interpersonal relationships and the self-esteem of patients, that is the reason the demand for aesthetic and conservative treatments are more frequent in dental practice, this demand commits professionals to a greater preparation, in order to identify the most appropriate procedures to be executed. For the dentist it is a challenge to achieve a complete harmonization and integration of the treatments carried out in the anterior sector and even more when it is necessary to replace a single dental element. The objective of this case report is to describe a highly complex rehabilitation case of a fractured upper central incisor, whose color and shape characteristics were recreated through a correct exchange of information between the dentist and the dental technician, obtaining a lithium disilicate crown with excellent mimicry.